On the Development of the Symbolic Meaning - Sargsyan, Marianna (Armenian Folia Anglistika, 2008)
The article studies the process of the establishment of the symbolic meaning of a word. The author presents the lexical groups making up the core vocabulary of a given language which undergo changes in meaning more often and take on a symbolic function. The article also presents the similarities and differences between the two key types of symbols – traditional and authorial.